Rational Design of Highly Efficient One‐pot Synthesis of Ternary PtNiCo/FTO Nanocatalyst for Hydroquinone and Catechol Sensing. Issue 1 (6th September 2020) - Awais, Azka; Arsalan, Muhammad; Sheng, Qinglin; Zheng, Jianbin; Yue, Tianli
Abstract: In this work, we present a simple and efficient method for preparation of widely dispersed PtNiCo nanocatalyst on FTO without the use of any heavy complex structure. The proposed nanocatalyst enhances the chemical interaction of PtNiCo/FTO and increases its catalytic activity, which was used for electrochemical sensing of catechol and hydroquinone. The surface morphology was characterized by TEM, HRTEM, and XRD. The size of the PtNiCo/FTO octahedrons nanocatalyst was about 0.35–4 nm. Gradual increase of concentration exhibited linearity in oxidation peak response up to 1100 μM with a low detection limit of 0.79 μM for HQ and 1.05 μM for CC. The sensitivity is 1035 μAmM −1 cm −2 for catechol and 1197 μAmM −1 cm −2 for hydroquinone. The prepared nanomaterial/sensor applied to real water samples with good reproducibility (98–99 %). Abstract :